Vitamin D deficiency is associated with increased human sinonasal fibroblast proliferation in chronic rhinosinusitis with nasal polyps - Carroll, William W. (Int Forum Allergy Rhinol, 2016)
BACKGROUND: Vitamin D3 (VD3) is a steroid hormone with known anti-proliferative properties. Patients with chronic rhinosinusitis with nasal polyps (CRSwNP) have been shown to be VD3 deficient. Moreover, VD3 deficiency is associated with worse disease in patients with CRSwNP. One cell type thought to play a role in chronic rhinosinusitis (CRS) is the human sinonasal fibroblast (HSNF). The aim of this study was to investigate VD3 deficiency and HSNF proliferation in CRSwNP. METHODS: Blood and sinus tissue explants were collected at the time of surgery from patients with CRSwNP (n=15). Control subjects (n=12) were undergoing surgery for cerebrospinal fluid leak repair or to remove non-hormone-secreting pituitary tumors. Ex-vivo HSNF proliferation was analyzed with flow cytometry using expression of fibroblast specific protein (FSP) and the proliferation marker Ki67. Plasma levels of 25-hydroxyvitaminD3 (25VD3) were measured by enzyme-linked immunosorbent assay. In vitro analysis of HSNF proliferation after treatment with 1,25VD3 was performed using carboxyfluorescein succinimidyl ester (CFSE) and analyzed with flow cytometry. RESULTS: In CRSwNP patients there was an inverse correlation between 25VD3 and proliferating HSNF (p= 0.0135). This correlation was not seen for control patients (p=0.3869). In vitro analysis showed that HSNF from patients with CRSwNP had a higher proliferation index at baseline than HSNF from control patients (p<0.01). When treated with 1,25VD3, there was a significant decrease in HSNF proliferation index in patients with CRSwNP (p<0.01), but not control patients. CONCLUSIONS: VD3 deficiency is associated with increased HSNF proliferation in CRSwNP. Further investigation into how HSNFs and VD3 impact CRSwNP pathophysiology is warranted.